LIMITATIONS OF PEGYLATED NANOCARRIERS: UNFAVOURABLE PHYSICOCHEMICAL PROPERTIES, BIODISTRIBUTION PATTERNS AND CELLULAR AND SUBCELLULAR FATES - Sebak, Aya Ahmed (International Journal of Applied Pharmaceutics, 2018)
Assuming that polyethylene glycol (PEG)-conjugated or PEGylated nanocarriers always offer outstanding physicochemical properties and pharmacokinetics profiles when compared to non-PEGylated ones, is not always accurate. For example, drug-loaded PEGylated nanocarriers for the treatment of cancer will not magically escape the reticuloendothelial system (RES) sequestration and clearance, benefit from the enhanced permeability and retention (EPR) effect of the tumor leaky vasculature and preferentially accumulate in the target tissue or cells. This is too good to be true. In this review, several drawbacks of PEGylation will be discussed; for example, how PEGylation can give rise to unfavourable physicochemical characteristics (e. g. particle size and release patterns) and post in vivo administration limitations of the formulated nanocarriers (e. g. limited evasion of RES uptake, development of hypersensitivity reactions, reduced intracellular accumulation and interference with the subcellular processing of nanocarriers necessary to produce the intended pharmacological effect). This review aims at providing better understanding of the pros and cons of PEGylation, encouraging the use of PEGylation with caution, avoiding the assumption that PEGylation will provide all advantages needed to deliver nanocarriers to the target tissue and looking for alternatives to optimize nanocarriers' utilization especially in the delivery of chemotherapeutic agents for the treatment of different types of cancer. This review comprises a summary of some of the reported literature between 2013 and 2018 using different search engines; PubMed, Science Direct and Google Scholar, and the keywords listed below.